Reducing Auditory Nerve Excitability by Acute Antagonism of Ca2+-Permeable AMPA Receptors - Walia, Amit; Lee, Choongheon; Hartsock, Jared; Goodman, Shawn S.; Dolle, Roland; Salt, Alec N.; Lichtenhan, Jeffery T.; Rutherford, Mark A. (Frontiers in Synaptic Neuroscience, 2021)
Hearing depends on glutamatergic synaptic transmission mediated by α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs). AMPARs are tetramers, where inclusion of the GluA2 subunit reduces overall channel conductance and Ca2+ permeability. Cochlear afferent synapses between inner hair cells (IHCs) and auditory nerve fibers (ANFs) contain the AMPAR subunits GluA2, 3, and 4. However, the tetrameric complement of cochlear AMPAR subunits is not known. It was recently shown in mice that chronic intracochlear delivery of IEM-1460, an antagonist selective for GluA2-lacking AMPARs (also known as Ca2+-permeable AMPARs (CP-AMPARs)), before, during, and after acoustic overexposure prevented both the trauma to ANF synapses and the ensuing reduction of cochlear nerve activity in response to sound. Surprisingly, baseline measurements of cochlear function before exposure were unaffected by chronic intracochlear delivery of IEM-1460. This suggested that cochlear afferent synapses contain GluA2-lacking CP-AMPARs alongside GluA2-containing Ca2+-impermeable AMPA receptors (CI-AMPARs), and that the former can be antagonized for protection while the latter remain conductive. Here, we investigated hearing function in the guinea pig during acute local or systemic delivery of CP-AMPAR antagonists. Acute intracochlear delivery of IEM-1460 or systemic delivery of IEM-1460 or IEM-1925 reduced the amplitude of the ANF compound action potential (CAP) significantly, for all tone levels and frequencies, by > 50% without affecting CAP thresholds or distortion product otoacoustic emissions (DPOAE). Following systemic dosing, IEM-1460 levels in cochlear perilymph were 30 % of blood levels, on average, consistent with pharmacokinetic properties predicting permeation of the compounds into the brain and ear. Both compounds were metabolically stable with half-lives > 5 hours in vitro, and elimination half-lives in vivo of 118 minutes (IEM-1460) and 68 minutes (IEM-1925). Heart rate monitoring and off-target binding assays suggest an enhanced safety profile for IEM-1925 over IEM-1460. Compound potency on CAP reduction (IC50 73 µM IEM-1460) was consistent with a mixture of GluA2-lacking and GluA2-containing AMPARs. These data strongly imply that cochlear afferent synapses of the guinea pig contain GluA2-lacking CP-AMPARs. We propose these CP-AMPARs may be acutely antagonized with systemic dosing, to protect from glutamate excitotoxicity, while transmission at GluA2-containing AMPARs persists to mediate hearing during the protection.